2020
DOI: 10.1101/2020.02.22.20025791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temperature Significantly Change COVID-19 Transmission in 429 cities

Abstract: Background There is no evidence supporting that temperature changes COVID-19 transmission. Methods We collected the cumulative number of confirmed cases of all cities and regions affected by COVID-19 in the world from January 20 to February 4, 2020, and calculated the daily means of the average, minimum and maximum temperatures in January. Then, restricted cubic spline function and generalized linear mixture model were used to analyze the relationships. Results There were in total 24,232 confirmed cases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
305
8
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(360 citation statements)
references
References 17 publications
28
305
8
6
Order By: Relevance
“…Thus, the arrival of summer could reduce the transmission of the COVID-19. Our result agreed with those already reported in other geographical locations, showing how the number of diagnosed cases increase below a maximum temperature of 10 ºC and linearly decreasing afterward (Triplett 2000;Wang et al, 2020b). However, these are cross-sectional studies at the country scale, which might have some measurement error due to high spatial variability when estimating a fixed temperature exposure for large geographic areas (Soares et al, 2012).…”
Section: Dear Editorsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the arrival of summer could reduce the transmission of the COVID-19. Our result agreed with those already reported in other geographical locations, showing how the number of diagnosed cases increase below a maximum temperature of 10 ºC and linearly decreasing afterward (Triplett 2000;Wang et al, 2020b). However, these are cross-sectional studies at the country scale, which might have some measurement error due to high spatial variability when estimating a fixed temperature exposure for large geographic areas (Soares et al, 2012).…”
Section: Dear Editorsupporting
confidence: 92%
“…A previous study in the four major Chinese cities suggested that the SARS outbreak was significantly associated with the temperature, increasing the daily incidence rate with lower temperatures (Tan et al, 2005). Recent preprint studies using national data from countries affected by COVID-19 reported that low temperature is beneficial to the viral transmission (Triplett 2020;Wang et al, 2020a;Wang et al, 2020b). However, these should be taken with caution since have not yet been peer reviewed.…”
Section: Dear Editormentioning
confidence: 99%
“…All analyses were conducted using R software (version 3.5.3) with the GAM fitted by the "mgcv" package (version 1. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The effect estimates were expressed as the percentage changes and their 95% confidence intervals (CIs) in daily mortality of COVID-19 associated with per 1 unit increase in weather variables.…”
Section: Methodsmentioning
confidence: 99%
“…Some evidence of a faster spreading of diseases in high humidity levels has been reported, 16 namely for the Legionella disease, although this infection is not caused by a virus. Few papers have been written since mid-February on this topic [17][18][19][20] even though the relationship is not perfectly established and more research is required.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%